(untitled) (Global Journal of Management and Business Research, 2020)
The purpose of this study is to investigate the effect of foreign direct investment and official development assistance on tax burden in Jordan employing the Auto-Regressive Distributed Lags Bounds Testing (ARDL BT) co-integration approach to the data ranging from 1991 to 2018. The results indicated that there is a long-run relationship among variables. The results showed that there is a positive and statistically significant effect of the ratio of foreign direct investment to GDP (FDI) on tax burden (TB) in the long run, and a positive and statistically significant effect of the ratio of official development assistance to GDP (ODA) on tax burden (TB) in the long run. The estimation results indicate that a 1% increase in (FDI) increases (TB) by 0.53%, and a 1% increase in (ODA) increases (TB) by 1.45%. This study is the first of its kind in examining the impact of foreign direct investment and official development assistance together on the tax burden in Jordan.